أثر تبني نظام إدارة الجودة إيزو 9000 على تحسين مؤشر المردودية في المؤسسات الاقتصادية الجزائرية - بربوشة, مريم (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة لقياس وتحليل قدرة المؤسسات الاقتصادية الجزائرية على تحقيق مؤشر مردودية موجب قبل وبعد تبنيها لنظام إدارة الجودة وحصولها على شهادة إيزو 9000 وتحديد أثر ذلك على التحسين من معدلات مردوديتها الاقتصادية. توصلت الدراسة إلى أن معظم المؤسسات المكونة لعينة الدراسة قادرة على تحقيق مردودية اقتصادية، غير أنها عرفت تدهور بعد تبنيها لنظام إدارة الجودة إيزو 9000، وهذا ما أيدته نتائج الاختبارات الإحصائية التي توصلت لعدم وجود أثر لتبني نظام إدارة الجودة على تحسين المردودية الاقتصادية بالمؤسسات محل الدراسة This study aims to measure and analyze the ability of Algerian economic firms to achieve a positive profitability index before and after they adopt the Quality Management System and obtain the ISO 9000 certification, and determining the impact of that on improving their economic profitability. The study found that most studied firms are able to achieve economic profitability, However, it experienced a deterioration after its adoption of the ISO 9000 Quality Management System, This was supporting by the results of statistical tests, which concluded that the adoption of a quality management system did not have an impact on improving the economic profitability in the firms under study.
The impact of adopting an "ISO 9000" quality management system to improve the profitability index in the Algerian economic firms
مقال
Keywords: إدارة الجودة ; نظام إدارة الجودة إيزو 9000 ; المردودية الاقتصادية